Деякі моделі динаміки міст - Навроцький, Д. О. (ХНУРЕ, 2024)
The evolution of an urban system can be mathematically described by a vector field in the phase space. An interpretation of the Wolterra equations in the context of problems of urban production and population migration, showing the possibility of their application to explain the phenomenon of urban development is given.
Keywords: система Лоренца; модель динаміки міста